Achieving very high PV penetration – The need for an effective electricity remuneration framework and a central role for grid operators. (September 2016) - Perez, Richard; Rábago, Karl R.; Trahan, Mike; Rawlings, Lyle; Norris, Ben; Hoff, Tom; Putnam, Morgan; Perez, Marc
Abstract: This article proposes that optimally deployed solutions to the intermittency introduced by high penetration solar – e. g., electrical storage, optimized curtailment and demand response – could affordably transform solar power generation into the firm power delivery system modern energy economies require, thereby enabling very high solar penetration and the displacement of conventional power generation. The optimal deployment of these high-penetration-enabling solutions imply the existence of a healthy power grid, and therefore imply a central role for utilities and grid operators. This article also proposes that a value-based electricity compensation mechanism (based on e.g., Value of Solar (VOS) and load shaping tariffs), recognizing the multi-facetted, penetration-dependent value and cost of solar energy, and capable of shaping consumption patterns to optimally match resource and demand, could be an effective vehicle to enable high solar penetration and deliver affordable firm power generation. Highlights: Intermittent PV generation can affordably be transformed into firm power generation. To achieve this objective, enabling solutions must be optimally deployed. These solutions include: storage, curtailment, geographic dispersion, load shaping. Their optimal deployment imply a central role for grid operators. A catalyst to their deployment is an effective electricity remuneration system.